NGHIÊN CỨU TỔNG HỢP VÀ ĐẶC TRƯNG HỆ XÚC TÁC HYDROTALCITE HAI THÀNH PHẦN Mg-Al CHO PHẢN ỨNG DECACBOXYL HÓA DẦU DỪA THU HYDROCACBON - Diệu Hồng, Nguyễn Khánh; Dũng, Hoàng Ngọc (Vietnam Journal of Science and Technology, 2015)
Hydrotalcite liked structure catalysts were prepared through co-precipitation method with varying the molar ratio of Mg/Al in nitrate salts from 2/1 to 4/1. The catalysis activity of four as-synthesized catalysts were also tested in decarboxylation process of coconut oil to find out what is the most suitable catalyst aimed to maximize liquid product owning the boiling range within that of fossil kerosene. The results showed that the catalyst with Mg/Al molar ratio of 3/1 was the best catalyst. The percentage of the liquid product with boiling range from 180 to 250oC was 25.2% wt. For further characterizations of the chosen catalyst, FT-IR and EDX were used and indicated a very precise and homogeneous distributions of the element component and structure in the catalyst after calcination at 500oC. Keywords: coconut oil, decarboxylation, hydrotalcite, co-precipitation.